Structure and photophysics of indigoids for singlet fission: Cibalackrot - Ryerson, Joseph L; Zaykov, Alexandr; Aguilar Suarez, Luis E; Havenith, Remco W A; Stepp, Brian R; Dron, Paul I; Kaleta, Jiří; Akdag, Akin; Teat, Simon J; Magnera, Thomas F; Miller, John R; Havlas, Zdeněk; et al. (The Journal of chemical physics, 2019)
We report an investigation of structure and photophysics of thin layers of cibalackrot, a sturdy dye derived from indigo by double annulation at the central double bond. Evaporated layers contain up to three phases, two crystalline and one amorphous. Relative amounts of all three have been determined by a combination of X-ray diffraction and FT-IR reflectance spectroscopy. Initially, excited singlet state rapidly produces a high yield of a transient intermediate whose spectral properties are compatible with charge-transfer nature. This intermediate more slowly converts to a significant yield of triplet, which, however, does not exceed 100% and may well be produced by intersystem crossing rather than singlet fission. The yields were determined by transient absorption spectroscopy and corrected for effects of partial sample alignment by a simple generally applicable procedure. Formation of excimers was also observed. In order to obtain guidance for improving molecular packing by a minor structural modification, calculations by a simplified frontier orbital method were used to find all local maxima of singlet fission rate as a function of geometry of a molecular pair. The method was tested at 48 maxima by comparison with the ab initio Frenkel-Davydov exciton model.